Determination of potentially toxic metals and natural radionuclides in airborne pollens produced different urban environments in Turkey and health risk assessment - Turhan, Şeref; Çeter, Talip; Altuner, Ergin Murat; Karabıcak, Serhat; Çeter, Selin; Bıyıklıoğlu, Oktay; Aktaş, Şeymanur; Kurnaz, Aslı (Informa UK Limited, 2024)
Air pollutants are associated with potentially toxic metals (PTMs) and natural and/or artificial radionuclides, which can pose a major threat to human and environmental health. Pollens can be utilized as a bioindicator to determine the level of air pollution in urban areas. In this study, the concentrations of PTMs and natural radionuclides in 35 airborne pollen samples of 22 species belonging to Pinaceae, Cupressaceae, Araucariaceae, Betulaceae, Salicaceae, and Oleaceae families grown in different urban areas in Turkey were determined using an energy-dispersive X-ray fluorescence spectrometry. For the first time, non-carcinogenic and radiologic health risk assessments for adults were done, estimating hazard index (HI) and annual effective dose (AED), respectively. The concentrations of Fe, Mn, Zn, Ti, Sr, Cu, Ni, Co, Cr, V and Pb analyzed in airborne pollen samples varied from 52.1 to 3078.0, 26.1 to 159.6, 15.6 to 199.7, 9.1 to 282.2, 1.0 to 128.4, 5.0 to 40.1, 5.4 to 23.6, <LD to 11.3, 1.6 to 26.6, <LD to 11.1 and <LD to 5.7 mg/kg, respectively. The average concentrations of K (2%), Th (1.3 mg/kg) and U (1.0 mg/kg) were converted into the activity concentrations (in Bq/kg) of 40K (595.8), 232Th (5.2) and 238U (11.8), respectively. All HI and AED values revealed a very low non-carcinogenic and radiological health risk due to exposure to all PTMs and radionuclides in the pollen samples studied.
Keywords: Radioisotopes; Air Pollutants; Turkey; Metals; Metals, Heavy; Pollen; Humans; Cities; Risk Assessment; Environmental Monitoring